2004
DOI: 10.1353/hpu.2004.0037
|View full text |Cite
|
Sign up to set email alerts
|

Patient Health Status and Appointment Keeping in an Urban Community Health Center

Abstract: This study examines the relationship between patient health status and the likelihood of missing appointments in a community health center serving low-income patients. Medical records of 465 adult patients scheduled to be seen during one week in February 1999 were audited for an 18-month period. Seventy-three percent of patients failed to keep one or more appointments; 43% missed one or two; 30% missed three or more. Health status measures significantly associated with missing appointments included depression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
4
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 16 publications
8
80
4
4
Order By: Relevance
“…This is consistent with the literature supporting the effects of intimate partner abuse on delayed access to HIV care and missed appointments 17 and with other studies illustrating the relationship between mental health and service utilization. 36,37 Additionally, poorer physical health was associated with a greater risk for more barriers to care. Treatment-specific and general social supports were associated with fewer reported barriers, though the association with treatment specific support was not significant in the adjusted model.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the literature supporting the effects of intimate partner abuse on delayed access to HIV care and missed appointments 17 and with other studies illustrating the relationship between mental health and service utilization. 36,37 Additionally, poorer physical health was associated with a greater risk for more barriers to care. Treatment-specific and general social supports were associated with fewer reported barriers, though the association with treatment specific support was not significant in the adjusted model.…”
Section: Discussionmentioning
confidence: 99%
“…4 Prior research has suggested that in primary care residency program practices, those more likely to miss scheduled appointments are younger adult, 1,4-6 unmarried, 5 nonwhite patients 4,6 who have larger families and less education 22,23 and whose language, race, or sex is not concordant with that of the clinician 2 ; patients who have no insurance 5 or are on Medicaid 4 ; patients new to the practice 5 ; patients referred from the emergency department 7 ; patients with acute rather than chronic illnesses 5 ; patients scheduled with fi rst-year residents or medical students 4 ; patients with a history of missed appointments 1,6,7 ; and patients with physician-identifi ed psychosocial problems. 3,6 Our fi ndings support some of these associations (no insurance, new patients) but not others (Medicaid, young adults). Interestingly, only 3 of the 11 rate exemplars (27%) and 4 of the 8 management exemplars (50%) used this kind of information from previous research to inform practice strategies.…”
Section: Work With Individual Residentsmentioning
confidence: 56%
“…; patients with acute rather than chronic illnesses 5 ; patients scheduled with fi rst-year residents or medical students 4 ; patients with a history of missed appointments 1,6,7 ; and patients with physician-identifi ed psychosocial problems. 3,6 Our fi ndings support some of these associations (no insurance, new patients) but not others (Medicaid, young adults). Interestingly, only 3 of the 11 rate exemplars (27%) and 4 of the 8 management exemplars (50%) used this kind of information from previous research to inform practice strategies.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Patients missing their appointments more likely young and socioeconomic deprived; best predictor was prior timeliness [1,11]. Most of them quoted "forgetfulness" as the main reason in addition to psychosocial problems, disappearance of health problems in the meantime or, in contrast, emergency access to hospitals due to worsening, urgent workplace requirements, child minding, public transport problems, exceeded waiting time until the appointment [1,2,5,18]. Lacey et al [13] distinguished emotional reasons, staff rudeness and lack of understanding for schedule systems.…”
Section: Introductionmentioning
confidence: 99%